Rho- Kinase Inhibitor Y-27632 Decreases the Thickness of Trabecular Meshwork in Juvenile Rats Mod-el Injected with Sodium Hyaluronate - Wino Vrieda Vierlia; Lely Retno Wulandari; Hidayat Sujuti; Ma'sum Effendi (Journal of Tropical Life Science, 2018)
Most glaucoma drugs lower the intraocular pressure (IOP) by decreasing the aqueous humor production and increasing the outflow through uveoscleral pathway. None of these drugs work mainly on increasing outflow through the trabecular pathway. Consequently, the experiment to develop glaucoma drugs directly target at the trabecular outflow pathway is highly required. The purpose of this study is to reveal the effect of rho-kinase inhibitor Y-27632 on the thickness of trabecular meshwork in juvenile rats model injected with sodium hyalu-ronate.  This study was an experimental study with posttest only control group design. Twenty-four rats were included in this study. Each eye of the rat would be considered as one sample. Samples were divided into 6 groups, negative control group, positive control I group with intracameral sodium hyaluronate injection, posi-tive control II group with topical Y-27632 10 mM, and three experimental groups with intracameral injection of sodium hyaluronate and Y-27632 10-1 mM, 1 mM, and 10 mM respectively. After the procedures all rats were sacrificed and enucleated. Trabecular meshwork tissue was stained with Hematoxilene-Eosin and evalu-ated under 400× microscopic magnification. Quantitative measurements were taken using computerized image analysis with dot slide program.  There were significant statistic differences among the positive control I group and the experimental groups (p-value < 0.05) as well as the positive control II group and the experi-mental groups (p-value < 0.05). The highest mean of decreasing trabecular meshwork thickness was noted in the group given by sodium hyaluronate and Y-27632 10 mM with value of 118.42 µm. There was decreasing thickness of trabecular meshwork due to the effect of rho- kinase inhibitor Y-27632 in juvenile rats injected with sodium hyaluronate.